IS PSYCHEDELIC TREATMENT OF MENTAL HEALTH DISORDERS READY FOR PRIME TIME? - Ashraf, Nauman (Journal of Pakistan Psychiatric Society, 2024)
Psychedelics, substances known to alter perception, mood, and consciousness, have been used across various cultures for centuries, often in religious ceremonies to facilitate spiritual experiences. Lysergic acid diethylamide (LSD) was used clinically from the 1950s until its ban in 1967. Recently, there has been a resurgence of interest in psychedelics for treating mental health disorders such as PTSD, anxiety, depression, and substance use disorders. The FDA has designated several psychedelic compounds as "breakthrough therapies," acknowledging their potential for safety and effectiveness. Psychedelics like Psilocybin, LSD, DMT/Ayahuasca, MDMA, Peyote, and Ketamine work through various mechanisms, including agonism at 5HT2A receptors and NMDA antagonism. These substances promote neuroplasticity and can disrupt pathological activity patterns in the brain’s default mode network (DMN), facilitating new perspectives and emotional processing. Psychedelic-assisted therapy leverages these properties to help patients gain insight into repressed conflicts and reduce maladaptive defenses. The therapeutic process involves preparation, support during dosing, and integration phases. Safety concerns include hallucinogen persisting perception disorder (HPPD), serotonin toxicity, and potential boundary violations. Despite promising early results, comprehensive research is needed to fully understand the therapeutic potential and limitations of psychedelics. Psychedelic-assisted therapy could offer hope and transformation for millions suffering from mental illnesses if proven safe and effective.